A rare foreign body in a patient with poor dentition: a satay skewer / V Sha Kri Eh Dam, Baharudin Abdullah and Irfan Mohamad - Dam, V Sha Kri Eh; Abdullah, Baharudin; Mohamad, Irfan (Faculty of Medicine, 2022)
Foreign body (FB) ingestion and impaction in the upper gastrointestinal tract is a common urgent referral to otorhinolaryngology. The types of FB are significantly different between children and adults, and it largely depends on the region, sociocultural influences and dietary habits of the patient. Rare FBs in adults should be suspected in certain groups of people with psychiatric illnesses and in patients with dental pathology who are unable to chew food properly before swallowing. In this report, we present a rare case of oesophageal impaction by a long satay skewer with sharp ends along with chicken meat in a 37-year-old man with poor dentition. It was successfully removed using rigid oesophagoscopy.